David Wolffsohn. Aufsteiger, Grenzgänger, Mediator: eine biographische Annäherung an die Geschichte der frühen Zionistischen Organisation (1897–1914) - Meybohm, Ivonne (Jüdische Religion, Geschichte und Kultur, 2013)
David Wolffsohn (1850s – 1914) was the closest assistant to Theodor Herzl and became his successor in the presidency of the World Zionist Organization in 1905. Using him as an example, this study shows how the World Zionist Organization, an internally quarelled, financially and politically uninfluential, loose affiliation in its modest beginnings finally succeeded in acting historically powerful.The study does not present a classical type of biography but an entangled history of a person and an institution, for which Meybohm chose the term »integrated biography«. By combining the methodological approaches of the new cultural history, social-, political and economic history, person as well as institution will be thoroughly analyzed. The multiperspectivity also covers Wolffsohns network, which includes his colleagues, supporters and opponents. It contextualizes the Zionist organization with other contemporaneous national movements as well as international emancipation movements, such as social democracy or the international women’s movement.Besides domestic and foreign politics, especially the Zionist commercial politics will be analyzed for it is as uninvestigated by recent scholarship as the life and work of Wolffsohn himself.The results of this integrated biography challenge earlier scholarship of Zionism which mostly presents a teleological reading of Zionist history based on the successful founding of the state of Israel in 1948. In contrast to this, using the example of Wolffsohn’s biography, it is possible to show, that the long range success of this extraordinary project could not be forseen in the beginning.